Aberrant methylation of MUC1 and MUC4 promoters are potential prognostic biomarkers for pancreatic ductal adenocarcinomas - Yokoyama, Seiya (Oncotarget, 2016)
Pancreatic cancer is still a disease of high mortality despite availability of diagnostic techniques. Mucins (MUC) play crucial roles in carcinogenesis and tumor invasion in pancreatic neoplasms. MUC1 and MUC4 are high molecular weight transmembrane mucins. These are overexpressed in many carcinomas, and high expression of these molecules is a risk factor associated with poor prognosis. We evaluated the methylation status of MUC1 and MUC4 promoter regions in pancreatic tissue samples from 169 patients with various pancreatic lesions by the methylation specific electrophoresis (MSE) method. These results were compared with expression of MUC1 and MUC4, several DNA methylation/demethylation factors (e.g. ten-eleven translocation or TET, and activation-induced cytidine deaminase or AID) and CAIX (carbonic anhydrase IX, as a hypoxia biomarker). These results were also analyzed with clinicopathological features including time of overall survival of PDAC patients. We show that the DNA methylation status of the promoters of MUC1 and MUC4 in pancreatic tissue correlates with the expression of MUC1 and MUC4 mRNA. In addition, the expression of several DNA methylation/demethylation factors show a significant correlation with MUC1 and MUC4 methylation status. Furthermore, CAIX expression significantly correlates with the expression of MUC1 and MUC4. Interestingly, our results indicate that low methylation of MUC1 and/or MUC4 promoters correlates with decreased overall survival. This is the first report to show a relationship between MUC1 and/or MUC4 methylation status and prognosis. Analysis of epigenetic changes in mucin genes may be of diagnostic utility and one of the prognostic predictors for patients with PDAC.